To Declaw or Not To Declaw, That is the Question: Behavior and Declaw Status of Cats in Suburban Massachusetts - Connolly, Kelly Elizabeth (Tufts Archival Research Center, 2019)
This paper focuses on a small, suburban geographic area to asses attitudes towards the practice of declawing in conjunction with the presence of physical and behavioral problems in declawed cats.; Thesis submitted for the MS in Animals and Public Policy degree.